Analysis of Transformational Leadership and Competence on Employee Performance with JoB Satisfaction as A Mediating Variable at The Uptd Animal Clinic Of The Agriculture And Livestock Office North Sumatra Province - Angga Pramudia; Husni Muharram Ritonga; Mesra B (Jurnal Fokus Manajemen, 2026)
Employee performance is a key factor in improving the quality of public services, especially in the animal health service sector. This study aims to analyze the effect of transformational leadership and competence on employee performance with job satisfaction as a mediating variable at the Animal Clinic Technical Implementation Unit (UPTD) of the North Sumatra Provincial Government's Plantation and Livestock Service. This study uses a quantitative approach with a survey method. The study population consisted of all 75 employees of the Animal Clinic UPTD, all of whom were included in the sample. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of the SmartPLS application. The results showed that transformational leadership and competence had a positive and significant effect on employee performance. In addition, transformational leadership and competence also had a positive and significant effect on job satisfaction. Job satisfaction was proven to have a positive and significant effect on employee performance. The results of the indirect effect test showed that job satisfaction was able to significantly mediate the effect of transformational leadership and competence on employee performance. The coefficient of determination value showed that transformational leadership, competence, and job satisfaction were able to explain 64.5% of the variation in employee performance. The findings of this study indicate that improving employee performance at the Animal Clinic Technical Implementation Unit of the North Sumatra Provincial Government's Plantation and Livestock Service can be achieved by strengthening transformational leadership, improving employee competency, and creating sustainable job satisfaction. This study is expected to be taken into consideration in the formulation of human resource management policies to improve the effectiveness of animal health services.